Research methods in intercultural communication : a practical guide - Hua, Zhu, 1970-; Ohio Library and Information Network (Malden, MA : Wiley-Blackwell, 2016)
"The focus is on the process of interaction and what the participants achieve out of the experience in terms of new values, identities and practices"--
Includes bibliographical references and index
Keywords: Intercultural communication -- Research; Intercultural communication -- Methodology; Electronic books